The influence of organizational culture, employee satisfaction, personality, and organizational commitment towards employee performance - Kawiana, I Gede Putu; Dewi, Luh Komang Candra; Martini, Luh Kadek Budi; Suardana, Ida Bagus Raka (International Research Journal of Management, IT & Social Sciences, 2018)
The present research was intended at determining the influence of organizational culture, employee satisfaction, and personality towards organizational commitment and employee performance. It was quantitative designed i.e., the relationship of causality for its variable. The research was conducted at Bank Perkreditan Rakyat (BPR) in Bali. The technique of collecting the data was used questionnaires to 135 employees of BPR in Bali. Data were analyzed through Structure Equation Modeling technique in AMOS 22.0 program. The results were obtained (1) the influence of organizational culture variable on organizational commitment was significant; (2) The influence of employee satisfaction variable on organizational commitment was significant; (3) The influence of personality variable on organizational commitment was significant; (4) The influence of organizational culture variable on employee performance interest was significant; (5) The influence of employee satisfaction variable on employee performance was significant; (6) The influence of personality variable on employee performance was significant; and (7) The influence of organizational commitment variable on employee performance was significant.